DETERMINANTS OF BLOOD CHOLINESTERASE LEVEL IN EMPLOYEES AT AN OIL PALM PLANTATION - DARFIKAL Atjo WAHYU, Lalu Muhammad SALEH, Masyitha MUIS, Anwar MALLONGI, MASNI, Afrisusnawati RAUF, Rizky MAHARJA, FAISAL, Mahfud YUSBUD, Munawir AMANSYAH, Afnal ASRIFUDDIN (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: The use of pesticides is one of the farmers effort to reduce pest disturbances. However, the use of pesticides has an adverse effect on health. This study aims to analyze the determinants that affect blood cholinesterase levels at oil palm plantation employees. Methods: This research was conducted using cross-sectional design. The population were all employees who worked in the spraying, fertilizing, and pesticide and fertilizer warehouse sections worked on oil palm plantations. The study sample consisted of 230 employees were selected by simple random sampling. Data were collected by using questionnaires and direct interviews regarding age, work period, nutritional status, and the use of personal protective equipment (PPE). Blood cholinesterase level was measured using the Tintometer Kit. Data analysis used Multiple Logistic Regression. Results: The results showed that there were two variables as determinant for blood cholinesterase levels, age (p=0.005) and the use of personal protective equipment (p=0.013), and there were two variables that were not determinant/risk factor for blood cholinesterase levels, years of service (p=0.424) and nutritional status (p=1.0).This study shows the importance of paying attention to age and the habit of using PPE for the activities related to pesticides in the workplace. Conclusion: The determinant factors of blood cholinesterase levels in employees of oil palm plantation are age and the use of PPE